An Energy Management System for microgrids including costs, exergy, and stress indexes. (December 2022) - Caliano, Martina; Delfino, Federico; Di Somma, Marialaura; Ferro, Giulio; Graditi, Giorgio; Parodi, Luca; Robba, Michela; Rossi, Mansueto
Abstract: In this paper, a multi-objective Energy Management System (EMS) for polygeneration microgrids is presented. The proposed tool has been developed within the LIVING GRID project, funded by the Italian Ministry of Research (actions related to the Italian Technology Cluster on Energy), and it is characterized by a detailed representation of generation units and flexible loads, as well as electric/thermal networks and storage systems that can be present in microgrids and sustainable districts. A new optimization model has been developed in which the objective function is related to the minimization of costs, the maximization of the overall exergy efficiency of the system, and the minimization of stress indexes. To solve efficiently the optimization problem, a novel algorithm based on an accelerated version of the Bregman Alternating Direction Method of Multipliers (with Heavy Ball dual acceleration term) has been developed and discussed. The decision model has been applied to a real case study represented by the Savona Campus of the University of Genova in Italy. A sensitivity analysis has been performed for evaluating the effect of each term of the objective function on the solution.